COMMUNITY PARTICIPATION IN VILLAGE BUDGET SUPERVISION IN BINUANG VILLAGE, BALUSU DISTRICT, BARRU REGENCY - Kasmiah Ali (Jurnal Scientia, 2022)
This study aims to find out: Community Participation in Supervision of Village Budgets in Binuang Village, Balusu District, Barru Regency. The type of research used is qualitative. The indicators in this study are community participation and village budgets. The formulation of the research problem is, (i) How is Community Participation in Village Budget Supervision in Binuang Village, Balusu District, Barru Regency. (ii) What are the Inhibiting Factors and Supporting Factors for Community Participation in Village Budget Supervision in Binuang Village, Balusu District, Barru Regency. Sources of data obtained through observation, interviews and documentation. The results of this study indicate that community participation in Binuang Village, Balusu District, Barru Regency is included in the good category. The factor that can hinder community participation in monitoring village budgets is that public awareness of the importance of overseeing village government budgets is still low. The supporting factors are the enthusiasm and desire of the community as well as the opportunity for the community to participate.